Tetrahedral Potassium-Aroxo-Cobaltate(II) Complexes - I. Ibrahim, Aisha (Asian Journal of Chemistry, 2010)
Potassium-aroxo-cobaltate(II) Complexes of the formula KCo ·nTHF (where, X = o–O2N, o-Cl, o-Br, m-Cl, p-Br, 2,4–, 2,6-dichloro and 2,4 dimethyl; n = 1 or 2) have been prepared. The various physico-chemical studies indicate that the tetrahedral streochemistry of these complexes. In comparison with the disodium-tetraaroxo- cobaltate(II) complexes, the steric hindrance caused by the large size of the potassium atom, suggested to be affected the 10 Dq values, the stability of the potassium-tri-aroxo-complexes, as well as their covalency nature.